THE USE OF THE THEORY OF PLANNED BEHAVIOR TO PREDICT FACTORS INFLUENCING PHYSICIANS' DECISION TO PRESCRIBE EXTEMPORANEOUS COMPOUNDING DOSAGE FORM FOR PEDIATRIC OUTPATIENTS - Wiedyaningsih, Chairun; Hakimi, Muhammad; Soenarto, Yati; Suryawat, Sri (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To explore the potential utility of the theory of planned behavior (TPB) in predicting intentions to prescribe extemporaneous compounding dosage form and to determine the salient beliefs associated with this intention. Methods: A cross-sectional survey design was utilized in this study. Participants of 249 physicians from Yogyakarta province completed a questionnaire based on the TPB. The questionnaires assessed TPB variables that are beliefs, attitude, subjective norm (SN), the perception of control, intention, and an additional variable of past behavior. The data were analyzed with multiple linear regressions. Results: Attitude, SN, and perception of control of the TPB components accounted for 58.6% of the variance in the prescribing intentions. The model was statistically significant (p<0.001). Attitude had the strongest impact on intentions. The additional variable of past behavior increased 61.9% to the explained variance in intentions (p<0.001). Participants' beliefs in the benefit of compounding prescription were the strongest predictor of the decision to prescribe. Conclusion: The TPB model provides information that attitudes, norms subektif, and perceived behavioral control were useful predictors for intentions to prescribe compounding. Past behavior variable increases the proportion to explain the variance of intention. The aAttitude was the most powerful predictor of physicians' intention to prescribe extemporaneous compounding dosage form for pediatric outpatient. Keywords: The theory of planned behavior, Extemporaneous compounding, Pediatric outpatients, Prescription.